2018
DOI: 10.7554/elife.38677
|View full text |Cite
|
Sign up to set email alerts
|

Current and future goals are represented in opposite patterns in object-selective cortex

Abstract: Adaptive behavior requires the separation of current from future goals in working memory. We used fMRI of object-selective cortex to determine the representational (dis)similarities of memory representations serving current and prospective perceptual tasks. Participants remembered an object drawn from three possible categories as the target for one of two consecutive visual search tasks. A cue indicated whether the target object should be looked for first (currently relevant), second (prospectively relevant), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 60 publications
(79 reference statements)
11
67
1
Order By: Relevance
“…For this reason, we characterize the priority-based transformations reported here as examples of remapping, not of recoding. This remapping account is also consistent with the findings of van Loon and colleagues [19], who observed that a classifier trained on a stimulus category when it was the PMI could also decode that category when it was the UMI, even though the pattern of activity of the UMI projected into an opposite region of multidimensional scaling space relative to the PMI. The characteristics underlying priority-based remapping may account for some of the mixed results in previous work on the effects of retrocuing.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…For this reason, we characterize the priority-based transformations reported here as examples of remapping, not of recoding. This remapping account is also consistent with the findings of van Loon and colleagues [19], who observed that a classifier trained on a stimulus category when it was the PMI could also decode that category when it was the UMI, even though the pattern of activity of the UMI projected into an opposite region of multidimensional scaling space relative to the PMI. The characteristics underlying priority-based remapping may account for some of the mixed results in previous work on the effects of retrocuing.…”
Section: Discussionsupporting
confidence: 89%
“…When a retrocue designated an item a UMI, IEM indicated that its representation in early visual cortex underwent a transformation that corresponded to a rotation of 90˚relative to how it was represented in the FoA. By extension, the present results also lend support to the interpretation of the priority-based transformation reported by van Loon and colleagues [19]. Because they observed a transformation of the posterior inferior temporal representation of objects in their study (cows, dressers, ice skates) to an "opposite" pattern in multidimensional scaling space, the general principle underlying priority-based remapping may be one of transforming the representation of deprioritized information into a format that is complementary to its representation when in the FoA, effectively maximizing the difference between an item when it is a UMI versus when it is a PMI.…”
Section: Stimulus Identitysupporting
confidence: 85%
See 3 more Smart Citations